The effects of intervention program on drug users and risk family: differences in understanding after participating in a family intervention program - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Alwi, Azlin; Mohamed Iqbal, Mimi Iznita (2015)
Family intervention programs have been found to be one of the effective strategies for educating the public, particularly high risks individuals (i.e., drug users and their family). In relation to this, a study was conducted to examine how high risks individuals’ understanding on parenting issues and skills changes after attending a family intervention program. It was hypothesized that the understanding of participants regarding parenting will increase after learning new techniques for effective parenting from the intervention program named Family on Alert Program (FoA). A total of 268 study participants from seven districts in peninsular Malaysia were enrolled, with average age between 41-50 years. All participants completed a questionnaire, which consisted of 30 questions regarding the program modules, both before and after the intervention program. Results show that a slight improvement of scores, albeit nonsignificant, was noted in post intervention, particularly in parenting styles, resilience, discipline and stress management modules. Overall, these results imply that there is insufficient evidence to draw a conclusion about whether or not the intervention program was effective. It is possible that other factors such as program duration, location, manpower issues, quality of program implementation, competencies of facilitators, and limitation of funds might account for the non-significant results. Implications and suggestions are discussed concerning the improvement and development of family-based interventions.